High Expression of ZNF208 Predicts Better Prognosis and Suppresses the Tumorigenesis of Breast Cancer - Jing Wei; Fangzheng Jiao; Xiaoya Wang; Yifan Qiao; Zihan Yuan; Fang Liu; Yan Fang; Yanfang Pan (Clinical Medicine Insights: Oncology)
Background: Breast cancer (BRCA), the hormone related malignant tumor, is well-known for poor prognosis. ZNF208 mainly acts as a transcription factor in various tumors, and the single nucleotide polymorphisms (SNPs) of ZNF208 are related to telomere length. Nevertheless, its role in breast tumorigenesis is largely unknown. Methods: We systematically investigated the gene expression, prognostic value, and promoter methylation of ZNF208 in BRCA with Gene Expression Profiling Interactive Analysis (GEPIA) and DNA Methylation Interactive Visualization Database (DNMIVD). Meanwhile, we clarified the association of ZNF208 with tumor-infiltrating immune cells (TICs) from Tumor Immune Estimation Resource (TIMER). Furthermore, we determined the biological process and functional enrichment from Cancer single-cell state atlas (CancerSEA). Finally, we verified our results with prognostic analysis and immunohistochemistry (IHC) assay. Results: We discovered that ZNF208 was downregulated in breast cancer, and low expression of ZNF208 predicted worse prognosis of BRCA patients. The promoter methylation level of ZNF208 was obviously increased, and ZNF208 was associated with TlCs in BRCA. In addition, ZNF208 could inhibit the metastasis and invasion biological processes, and regulate the MAPK and RAS signaling pathways in BRCA. Conclusion: Our findings illustrate that ZNF208 can function as a tumor suppressor and predict prognosis of breast cancer.